Epistemological status of the meme and memetic categories. A systematic review - Loayza Maturrano, Edward Faustino (2024)
The purpose of this article was to organize the conceptualization of the terms "meme" and "memetics" to define them extensively and intensively. The study is theoretical-hermeneutic based on a search and review of the use of the meme and memetic categories in research published in the course of the 21st century. The result of the analysis identifies that the term meme does not have a stable referent or a solid conventional content, which makes it difficult to formulate valid definitions. It was determined that the meme classifications do not correspond to logical norms and turn out to be narrowly focused typological descriptions. It was found that memetics does not have the attributes of a science; since it is constituted by an interdisciplinary matrix of eclectic knowledge, whose objective is the analysis of Internet memes, which are objects with a problematic epistemological status. It is concluded that the meme can be analyzed as a form of non-scientific knowledge within a non-classical epistemology program; and that the study of the meme provides a heuristic contribution in terms of evolutionary and social epistemology, since memetics broadens its thematic areas.